Analysis of morbidity and mortality from cervical cancer in the Samara region for 10 years - Irina V. Okuneva; Tatyana G. Zolotareva; Andrei E. Orlov (Наука и инновации в медицине, 2022)
Aim to study the dynamics of morbidity and mortality from cervical cancer, the age characteristics of the patients for the period 2010-2019 in the Samara region.